EFFECT OF STATIN ADJUVANT THERAPY ON IL-6, LIPID PROFILE EXAMINATION AND CLINICAL SYMPTOMS IN SCHIZOPHRENIC PATIENTS TREATED WITH RISPERIDONE - Ardiansyah, Syamsuddin Saidah; Liaury Kristian; Seweng Arifin; Limoa Erlyn; Bahrun Uleng; Lisal T Sonny (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Schizophrenia is a mental illness caused by gene-environment interaction. There is a role for dysregulation of inflammation in the pathogenesis of schizophrenia which is characterized by increased levels of interlukin-6. The use of first-generation antipsychotics can cause negative symptoms of schizophrenia. Treatment using anti-inflammatory adjuvants has the potential to have a better effect by reducing negative symptoms. Statins have been introduced as anti-inflammatory agents that can be used as adjuvant therapy for schizophrenia. Objective: To determine the effect of adjuvant statin therapy on IL-6, lipid profile and clinical symptoms in schizophrenic patients treated with risperidone. Methods: This study is an experimental study with a randomized clinical trial design with a double-blind approach. The study was conducted on 36 schizophrenic patients who were treated at Dadi Regional Special Hospital, South Sulawesi Province. Patients were randomized into 2 groups: 18 patients were given 4-6 mg/day of risperidone and 40 mg/day of oral simvastatin adjuvant therapy for 8 weeks (treatment) and 18 patients were given 4-6 mg/day of risperidone (control). A total of 18 healthy individuals were used to control IL-6 levels. IL-6 levels and lipid profiles were measured in the form of triglyceride, cholesterol, HDL and LDL levels before therapy and the 8th week. PANSS clinical symptoms were measured before therapy, week 4 and 8 after therapy. Data were analyzed using the independent sample t test, Mann Whitney, Wilcoxon, Spearman correlation and chi square. Results: IL-6 levels in schizophrenic patients were significantly higher than healthy individuals and IL-6 levels after both therapy with and without statin adjuvants were not significantly different from IL-6 levels in healthy individuals. There was a significant decrease in serum IL-6 levels in the treatment group, but not in the control group. Nonetheless, changes in serum IL-6 levels after 8 weeks of therapy were not significantly different between the treatment and control groups. There was a significant change in lipid profile in the treatment group, but not in the control. Lipid profile changes after 8 weeks of therapy differed significantly between the treatment and control groups. In the treatment group there was a decrease in triglyceride, cholesterol and LDL levels and an increase in HDL levels. There was a significant improvement in the clinical symptoms of schizophrenia patients in the treatment and controls at the 4th and 8th week of therapy. There were significant differences in changes in clinical symptoms between the treatment and the controls. IL-6 levels in schizophrenic patients receiving statin adjuvant therapy were not significantly associated with clinical symptoms. Conclusion: Simvastatin adjuvant therapy orally 40 mg/day for 8 weeks can reduce clinical symptoms, reduce serum IL-6 levels and clinical symptoms better than therapy with risperidone alone.